Bepaling van flottasieparameters deur middel van 'n laboratoriumapparaat. - Erasmus, Pieter Ernst (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.Ing.) -- Universiteit van Stellenbosch, 1980.